2019
DOI: 10.1186/s13104-019-4763-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct qPCR is a sensitive approach to detect Mycoplasma contamination in U937 cell cultures

Abstract: Objective: We aim to directly detect Mycoplasma DNA in a U937 suspension cell culture without using DNA purification. In order to make Mycoplasma contamination monitoring easier, we optimized a commercially available quantitative PCR (qPCR)-based detection kit. We compared the sensitivity of direct qPCR against qPCR with a purified DNA template. Results: Our findings indicate that qPCR worked optimally with a 6 μl sample volume and a 52 °C annealing-extension temperature. We were able to decrease the annealing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
1
0
3
Order By: Relevance
“…The direct RT-PCR in the application of DNA viral detection has shown promising results in hepatitis B and Mycoplasma organisms [ 21 , 22 ]. Other studies using direct RT-PCR on detecting viral RNA suggested that the use of PCR enhancers could lead to early RNAase release, which compromises the RNA integrity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct RT-PCR in the application of DNA viral detection has shown promising results in hepatitis B and Mycoplasma organisms [ 21 , 22 ]. Other studies using direct RT-PCR on detecting viral RNA suggested that the use of PCR enhancers could lead to early RNAase release, which compromises the RNA integrity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mikoplazmalar nispeten esnek hücre zarına sahip, çok küçük organizmalar oldukları için (0,3-1 μm) yaygın olarak kullanılan 0,45 µm mikrobiyolojik filtrelerden geçebilirler ve potansiyel olarak laboratuvardaki tüm kültürlere yayılabilir 20 . Bu organizma hücre fizyolojisi ile ilgili pek çok parametreyi değiştirebilir, bu da kontamine hücrelerle yapılan deneyleri değersiz hale getirir 34 .…”
Section: Discussionunclassified
“…Halihazırda kültüre edilen hücrelerin %10-15'inin mikoplazma ile kontamine olduğu tahmin edilmektedir 19 . Mikoplazma kontaminasyonunun hücre büyümesi, amino asit metabolizması, kromozomal anormalliklerin indüksiyonu, lenfosit aktivasyonunun indüksiyonu veya inhibisyonu, sitokinlerin indüksiyonu veya baskılanması ve hatta sinyal transdüksiyonu üzerinde etkisi vardır ve hücre kültürü çalışmaları açısından önemli bir tehdittir 20,35 . Mikoplazma tespitinde 4′,6-diamidino-2-phenylindole (DAPI) ve Hoechst işaretleme, PCR, q-PCR ya da kitler sıklıkla kullanılmaktadır [21][22][23] 38 .…”
Section: Discussionunclassified
See 1 more Smart Citation